Genomic and Molecular Abnormalities in Gynecologic Clear Cell Carcinoma. (February 2020) - Marks, Eric I.; Brown, Victoria S.; Dizon, Don S.
Abstract : Gynecologic clear cell carcinoma is a rare histology, accounting for 5% of all ovarian and endometrial cancers in the United States. Compared to other types of gynecologic cancer, they are generally less responsive to standard therapy and have an overall worse prognosis. In addition, mounting evidence suggests that the landscape of genetic and molecular abnormalities observed in these tumors is distinct from other cancers that arise from the same sites of origin. On a molecular level, these tumors characteristically display upregulation of the PI3K-AKT-mTOR and RAS-RAF-MAPK signaling axes, frequent loss of ARID1a, and overexpression of MDM2. Evidence also suggests that these tumors are more likely to express programmed death ligand 1 or demonstrate microsatellite instability than other gynecologic cancers. Despite these important differences, there has been relatively little investigation into histology-specific treatment of clear cell gynecologic cancers, representing an opportunity for new drug development. In this article, we review the unique genetic and molecular features of gynecologic clear cell cancers with an emphasis on potential therapeutic targets. The results of completed studies of treatment for clear cell carcinoma are also presented. We conclude with a discussion of ongoing clinical trials and potential avenues for future study.